Mali’s agrifood system structure and drivers of transformation - Pauw, Karl; Randriamamonjy, Josee; Thurlow, James; Diao, Xinshen; Ellis, Mia (International Food Policy Research Institute, 2023)
Mali experienced modest annual economic growth of 4.4 percent between 2009 and 2019 (INSTAT 2020; World Bank 2023a). With annual population growth of 3.0 percent during that period, the living standards of Malian people improved only modestly. In 2020, the global COVID-19 pandemic caused a significant slowdown in economic growth, while an increase in armed insurgencies by domestic terrorist groups also had an adverse effect on the economy. Mali’s GDP growth is projected to reach 4.0 percent in 2023 and 2024 (World Bank 2023b), suggesting the economy is inching back toward its prepandemic growth trajectory. Agriculture remains an important sector, accounting for 40 percent of GDP and more than 60 percent of employment in Mali. In this brief, we unpack the historical and projected economic growth trajectory further to better understand the role of agriculture as well as the broader agrifood system (AFS) in the performance and transformation of the economy of Mali.